THE “SOFTPOWER” POLICY OF TURKEY TOWARDS GEORGIA - L. M. Aleksanyan (Vestnik MGIMO-Universiteta)
South Caucasus throughout history was at the epicenter of clashes of different religions, civilizations, nations and states. At present moment the interests of both regional (Turkey, Iran) and global actors (the United States, NATO, the EU, Russia and others.) intersect in the region. Global transformations, changing power relations in international relations have their direct influence on the political processes taking place in the region. These processes are also linked with the activities of Turkey, which aspire to regional leadership. It is Georgia, which serves as a corridor between Turkey and states of Central Asia and the South Caucasus. Turkey spreads its influence in Georgia in almost all areas using economic, military and political tools, as well as the Russian-Georgian deteriorated relations. To achieve its goals, Turkey is actively pursuing a strategy of "soft power", which further strengthens its influence in the country. Public diplomacy is a part of soft power, which also ensures the formation of a positive and attractive image of Turkey in Georgia. This article investigates the contemporary policy of "soft power" of Turkey towards Georgia. It analyses the basic tools, institutions and the direction of this policy, actively implemented by the Republic of Turkey. Particular attention is paid to the activities of the Gulen Movement in Georgia. The author makes general conclusions regarding the effectiveness of this policy.